Penanaman Nilai-Nilai Tanggung Jawab Dan Kemandirian Pada Anak Di Lingkungan Panti Asuhan (Studi Kasus di Yayasan Yatim Muhammadiyah di Desa Kliteh, Kecamatan Sragen Tengah Kabupaten Sragen Tahun 2015) - Cahyaningrum, Ratri, Dra. Sri Arfiah, SH, M.Pd (2015)
This study aims to determine the form and manner of planting the values ​​of responsibility and independence in children in the orphanage orphan Muhammadiyah Sragen. This research method is a single case study spikes due to focus on a case in detail and subjects under study consists of one unit and limited to the aspects that have been directed at assessment purposes. Techniques of collecting data using interviews, observation, and documentation. The results showed that: 1) Form of planting anti care responsibilities Orphan dip Muhammadiyah Sragen is through the three principles of parenting is teaching, Rewarding and persuasion; 2) Form of planting independence, namely through guidance to prepare yourself and do the work related to the needs of self; 3) How to instill the value of responsibility by fostering religion, because the religion of the children's personal development responsible will be formed by itself so that they can know what is right and what is wrong; 4) How to instill the value of self-reliance that is trained to be independent in doing any daily activities within the orphanage. Keywords: Responsibility, Independence